2015
DOI: 10.3390/ijms160510214
|View full text |Cite
|
Sign up to set email alerts
|

Response of Different Genotypes of Faba Bean Plant to Drought Stress

Abstract: Drought stress is one of the major abiotic stresses that are a threat to crop production worldwide. Drought stress impairs the plants growth and yield. Therefore, the aim of the present experiment was to select the tolerant genotype/s on the basis of moprpho-physiological and biochemical characteristics of 10 Vicia faba genotypes (Zafar 1, Zafar 2, Shebam, Makamora, Espan, Giza Blanka, Giza 3, C4, C5 and G853) under drought stress. We studied the effect of different levels of drought stress i.e., (i) normal ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
91
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(116 citation statements)
references
References 38 publications
23
91
0
2
Order By: Relevance
“…Rapeseed could use physiological modifications in a similar way to adapt to soil water deficits. The maintenance of a high plant water status during stress is an important defensive mechanism to retain enough water by minimizing water loss15. Stomatal closure under drought is also an avoidance strategy to save water and maintain turgor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapeseed could use physiological modifications in a similar way to adapt to soil water deficits. The maintenance of a high plant water status during stress is an important defensive mechanism to retain enough water by minimizing water loss15. Stomatal closure under drought is also an avoidance strategy to save water and maintain turgor.…”
Section: Discussionmentioning
confidence: 99%
“…The studies at the proteome level in plants under drought stress have been carried out in many crops, including rice12, maize10, wheat11, barley9, cotton13, chickpea14, faba bean15, and sugar beet16. Many proteomics studies on the effects of abiotic stresses are available for rapeseed, but only a few proteomic analyses under drought stress were conducted.…”
mentioning
confidence: 99%
“…The increases in O2 -and H2O2 reveal the water limitation into plant cells, and consequent formation of reactive oxygen species (ROS), being that these composts promote the lipid peroxidation (Siddiqui et al, 2015), and induce the deterioration of the membranes, described by the increases of MDA and EL. Increases in ROS levels under water deficit conditions are associated with low efficiency in the excitation energy dissipation, through the photosynthetic apparatus, which it is considered an important source of overproduction of ROS under abiotic stress (Hura et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…There was significance increase in proline content (μmol g -1 .FW) in water stress treatment as compared with un-stressed water treatment. Research evidence has shown that proline is commonly produced in higher plants and generally accumulates in large extent in response to environmental stresses such as water stress and /or drought (Ashraf and Foolad, 2007;Kapuya et al, 1995;Lobato et al, 2008;Siddiqui et al, 2015;Tatar and Gevrek, 2008) and hence serving as a bio indicator of resistance or tolerance to water deficit (Bates et al, 1973). In a closely related study, Sanchez et al, (1998) reported increased proline content in pea plants subjected to drought stress.…”
Section: Vulgaris (L) Varietiesmentioning
confidence: 99%
“…Once plants accumulate proline in their tissues, the proline tends to reduce the toxic effects of ions in enzymes activity and also lowers the generation of free radicals formed by abiotic stresses (Siddiqui et al, 2015). The theory behind proline is therefore very useful to assess the physiological status and more generally to understand stress tolerance in plants species.…”
Section: Issn: 2319-7706 Volume 6 Number 3 (2017) Pp 2205-2214mentioning
confidence: 99%